Comparison of Efficacy and Safety Between Immunotherapy and Docetaxel Monotherapy in NSCLC Patients - Yang, Wenchao; Xuan, Bixia; Chen, Mengqi; Li, Xiaofang; He, Jiana; Si, Haiyan; Zhang, Yefei (Frontiers in Oncology, 2022)
Objective Meta analysis was used to compare the efficacy and safety of immune checkpoint inhibitor and docetaxel in the treatment of non-small cell lung cancer. Methods CNKI, CBM, PubMed, EMBASE, Cochrane Library, web of science and other databases were searched by computer. The randomized controlled trials of immune checkpoint inhibitors and docetaxel in the treatment of NSCLC published up to February 2022 were collected. Two researchers searched independently. The literature was screened and the data were extracted according to the nanodischarge standard. Revman5.4. The included studies were statistically analyzed. Results A total of 8 RCTs were included, including 2444 cases treated with immune checkpoint inhibitors and 2097 cases treated with docetaxel. Compared with docetaxel, the overall survival (HR = 1.40, 95%CI: 1.30-1.50, P < 0.00001) and progression free survival (HR = 1.22, 95%CI: 1.13-1.32, P < 0.00001) of NSCLC treated with ICIs were longer and more effective. The risk ratio of any grade of adverse reactions (HR = 0.41, 95%CI: 0.32-0.52, P < 0.00001) and above grade III adverse reactions (HR = 0.27, 95%CI: 0.18-0.41, P < 0.00001) in the treatment of NSCLC with ICIs was lower and the safety was better. Conclusion Compared with docetaxel, immune checkpoint inhibitor treatment can improve the clinical efficacy of NSCLC patients and has a lower incidence of adverse reactions. This treatment may be a promising treatment for NSCLC patients.